How do tourists react to political violence? An empirical analysis of tourism in Egypt - David Fielding; Anja Shortland (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper uses a detailed database of political violence in Egypt to study European and US tourists' attitudes towards travelling to a conflict region. We use time series analysis to study the heterogeneous impacts of different dimensions of political violence and counter-violence on tourist flows to Egypt in the 1990s. We find that both US and EU tourists respond negatively to attacks on tourists, but do not appear to be influenced by casualties arising in confrontations between domestic groups. However, European tourists are sensitive to the counter-violence measures implemented by the Egyptian government. There is also evidence of tourism in Egypt being affected by the Israeli / Palestinian conflict, with arrivals of tourists into Egypt rising when fatalities in Israel increase.
Keywords: P48; L83; 330; Tourism; Political Violence; Egypt